Supplementation of lentinan improves lactation performance by altering ruminal microorganisms and metabolites in dairy cows - Lun Tan; Xiao Li; Caiyun Fan; Dian Wang; Shuaihong Li; Yuhang Ding; Zixi Yang; Zhao Zhuo; Jianbo Cheng (Animal Nutrition)
Lentinan (LNT) is a bioactive polysaccharide that has been proven to improve the production performance of animals. The objective of this study was to investigate the effects of LNT on lactation performance and rumen fermentation in dairy cows. Through random block design, 80 Holstein cows were randomly assigned to four treatments (CON, control group, fed a basal diet; and 5LNT, 10LNT, 15LNT groups, fed a basal diet with 5, 10, 15 g/d LNT, respectively) according to the days in milk (57 ± 21.3 d), milk yield (42.3 ± 7.88 kg/d) and parity (3.44 ± 1.45). Each treatment had 20 replicates of one cow each. The results showed that there was a linear increment in the production of milk (P = 0.034, increased by 3.28 kg/d), milk protein (P = 0.020, increased by 76.04 g/d) and lactose (P = 0.003, increased by 213.07 g/d) with the increase in LNT doses. In addition, the apparent digestibility of crude protein (CP) linearly increased with the increasing LNT supplementation (P = 0.008, increased by 15.42%). In terms of ruminal fermentation, oxidation-reduction potential value (P = 0.001, reduced by 35.89), the proportion of acetate (P = 0.004, reduced by 8.91%) and acetate to propionate ratio (A/P; P = 0.002, reduced by 1.27) linearly decreased, while the proportion of propionate (P = 0.003, increased by 6.42%) and butyrate (P = 0.037, increased by 2.49%) linearly increased with the increase in LNT dosages. The changes in ruminal fermentation parameters led to changes in the ruminal microbiota and metabolites. Supplementation with LNT increased the relative abundance of some beneficial bacteria, such as Muribaculaceae and Lachnospiraceae (P < 0.05), and decreased the relative abundance of some harmful bacteria, such as Rhodobacteraceae, Tyzzerella, Lysinibacillus and Turicibacter (P < 0.05). Moreover, LNT supplementation up-regulated 2-(pyridin-2-ylamino) benzoic acid and hippuric acid (P < 0.05), which could promote phenylalanine metabolism, and down-regulated some metabolites inhibiting arginine biosynthesis, like 2-methylglutaric acid and N2-acetylornithine (P < 0.05). Moreover, lentinan supplementation significantly elevated 2-(pyridin-2-ylamino)benzoic acid (Py-PABA) and hippurate (P < 0.05), metabolites associated with enhanced phenylalanine metabolism, while reducing inhibitors of arginine biosynthesis such as 2-methylglutaric acid and N²-acetylornithine (P < 0.05). In conclusion, supplementation of LNT could improve the ruminal microbiota and metabolism and further affect the lactation performance of cows.